Experimental investigation of a bi-leaflet heart valve - Chan, Kah Ming (2016)
Babies with congenital heart defects require high risk surgeries at birth or adolescence. As the patient matures, replacement of larger artificial valves to accommodate their growth would require additional surgeries. The objective of this experiment is to reduce the amount of re-surgeries required by determining the compatibly of the artificial valves upon the change in diameters of the artery with growth and the method of which the valve was sutured.